I will solve your system by substitution.<span><span><span><span>2x</span>+<span>3y</span></span>=2</span>;<span><span>x+<span>6y</span></span>=<span>4x</span></span></span>Step: Solve<span><span><span>2x</span>+<span>3y</span></span>=2</span>for x:<span><span><span><span>2x</span>+<span>3y</span></span>+<span>−<span>3y</span></span></span>=<span>2+<span>−<span>3y</span></span></span></span>(Add -3y to both sides)<span><span>2x</span>=<span><span>−<span>3y</span></span>+2</span></span><span><span><span>2x</span>2</span>=<span><span><span>−<span>3y</span></span>+2</span>2</span></span>(Divide both sides by 2)<span>x=<span><span><span><span>−3</span>2</span>y</span>+1</span></span>Step: Substitute<span><span><span><span>−3</span>2</span>y</span>+1</span>forxin<span><span><span>x+<span>6y</span></span>=<span>4x</span></span>:</span><span><span>x+<span>6y</span></span>=<span>4x</span></span><span><span><span><span><span><span>−3</span>2</span>y</span>+1</span>+<span>6y</span></span>=<span>4<span>(<span><span><span><span>−3</span>2</span>y</span>+1</span>)</span></span></span><span><span><span><span>92</span>y</span>+1</span>=<span><span>−<span>6y</span></span>+4</span></span>(Simplify both sides of the equation)<span><span><span><span><span>92</span>y</span>+1</span>+<span>6y</span></span>=<span><span><span>−<span>6y</span></span>+4</span>+<span>6y</span></span></span>(Add 6y to both sides)<span><span><span><span>212</span>y</span>+1</span>=4</span><span><span><span><span><span>212</span>y</span>+1</span>+<span>−1</span></span>=<span>4+<span>−1</span></span></span>(Add -1 to both sides)<span><span><span>212</span>y</span>=3</span><span><span><span><span>212</span>y</span><span>212</span></span>=<span>3<span>212</span></span></span>(Divide both sides by 21/2)<span>y=<span>27</span></span>Step: Substitute<span>27</span>foryin<span><span>x=<span><span><span><span>−3</span>2</span>y</span>+1</span></span>:</span><span>x=<span><span><span><span>−3</span>2</span>y</span>+1</span></span><span>x=<span><span><span><span>−3</span>2</span><span>(<span>27</span>)</span></span>+1</span></span><span>x=<span>47</span></span>(Simplify both sides of the equation)Answer:<span><span>x=<span><span><span>4/7</span><span> and </span></span>y</span></span>=<span>2/<span>7
is what i got sorry if it don't help</span></span></span>
Answer:
The tip would be approximately $2.33. The total amount of money that should be left on the bill is $17.73.
Step-by-step explanation:
To determine the tip: 15.50 times 0.15 = 2.325 ≈ 2.33
To determine the total: 15.50 plus 2.33
Answer:
B
Step-by-step explanation:
Given
(4x + 3)(3x - 4)
Each term in the second factor is multiplied by each term in the first factor, that is
4x(3x - 4) + 3(3x - 4) ← distribute both parenthesis
= 12x² - 16x + 9x - 12 ← collect like terms
= 12x² - 7x - 12
The coefficient of the x- term is - 7 → B
Answer:
Q=5(2)+2(6)
Q=10+12
Q=22
22 is your answer
Step-by-step explanation:
Answer:
19 people passed
Step-by-step explanation:
19 people passed the test